Let’s play a new game: the drivers of eSports consumption (Research, Society and Development, 2021)
Despite the growth and economic relevance of electronic sports (eSports), the motivations of this type of media and entertainment consumption remain underexplored, particularly in scenarios in which traditional sports are a cultural element and an important influence in the lifestyle of the population. Thus, the main objective of this paper is to understand the drivers of electronic sports motivation for the Brazilian eSports audience, regarding their motivations to watch online matches. We performed a survey with 262 Brazilian eSports spectators, analyzing the results through Structural Equation Modeling. Findings revealed that that eSports consumption is driven by four main motivations, namely, novelty, escapism, aesthetic and vicarious achievement, being vicarious achievement the main driver of eSports consumption in Brazil. This study advances the understanding of the influence of culture in eSports consumption, exploring the antecedents of this kind of media entertainment and the role of motivations in the digital arena. This comprehension is paramount due to the increase of digital platforms, digital types of entertainment and the growth of eSports consumption worldwide.